2008
DOI: 10.1016/j.compositesa.2008.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Full field monitoring of the resin flow and laminate properties during the resin infusion process

Abstract: The resin infusion process (a.k.a. VARTM, SCRIMP) has developed as a low cost method for manufacturing large fibre reinforced plastic parts. This process still presents some challenges to industry with regards to reliability and repeatability, resulting in trial and error development being expensive and inefficient. This paper describes a fully instrumented resin infusion setup, providing preliminary experimental data acquired while varying influential parameters during the filling and post-filling stages. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(98 citation statements)
references
References 31 publications
7
86
0
5
Order By: Relevance
“…We have tested the model with both constant and tensorial permeability for the preform (porous) medium and the results showed a reasonable agreement with the ones presented in similar studies [1,2,3]. Presence of different regions with different permeability and porosity has also been studied and the results showed that such a layup configuration may lead to an unsaturated region in the domain.…”
Section: Resultssupporting
confidence: 64%
See 4 more Smart Citations
“…We have tested the model with both constant and tensorial permeability for the preform (porous) medium and the results showed a reasonable agreement with the ones presented in similar studies [1,2,3]. Presence of different regions with different permeability and porosity has also been studied and the results showed that such a layup configuration may lead to an unsaturated region in the domain.…”
Section: Resultssupporting
confidence: 64%
“…Its main intention is to provide a sustainable and consistent framework for the implementation and application of model concepts, constitutive relations, discretizations and solvers [5]. Figure 2(a), and they are similar to the results presented in the studies [1,2,3]. As seen in the figure, the resin fast fills up the distribution medium region, and then starts to impregnate the preform region.…”
Section: Numerical Implementationsupporting
confidence: 72%
See 3 more Smart Citations